Prediksi Kualitas Laba Dari Ukuran Perusahaan, Likuiditas Dan Struktur Modal Pada Perusahaan Pertambangan Di Bursa Efek Indonesia - Irawan irawan; Rafika Ardianti (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine the effect of firm size, Liquidity and Capital Structure on Earnings Quality in Mining Companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Data was collected by the documentation method. This research has a population of 47 mining companies listed on the Indonesia Stock Exchange with a sample selection method using purposive sampling and obtained 13 companies. Hypothesis testing was carried out using panel data regression analysis. The results of this study indicate: (1) Firm Size has a positive and significant effect on Earnings Quality. (2) Liquidity has a positive and significant effect on Earnings Quality. (3) Capital structure has a negative and insignificant effect on Earning Quality. Changes that occur in the sample company sample of 69% are caused by Company Size, Liquidity and Capital Structure, while the remaining 31% is determined by other variables not listed in this study.